Rancang Bangun Sistem Scrambler Komunikasi Radio VHF FM dalam Operasi TNI Angkatan Laut dengan Metode Quality Function Deployment (QFD) - Afran Fatchurrozi; Iwan Vanany (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2025)
Increased visits from foreign naval vessels to Indonesian ports have introduced strategic risks to secure military communications, particularly during joint exercises and limited naval operations. Traditional VHF FM radios aboard KRI units lack encryption capabilities, leaving transmitted data vulnerable to interception. To address this critical gap, this study designs and tests a secure scrambling system integrated into VHF FM radios, using the Quality Function Deployment (QFD) method to align system features with user needs. The research stages include collecting Voice of Customer (VoC) data from naval personnel, validating and analyzing key attributes, constructing Phase 1 and Phase 2 House of Quality matrices, and developing a frequency inversion-based scrambler prototype. Key technical priorities identified include flexible signal scrambling, ergonomic console layout, enhanced reliability, and GPS based position tracking. The scrambler was field-tested by 30 personnel aboard KRI vessels. Findings reveal a significant improvement over 20% in communication comfort, usability, and confidentiality compared to conventional systems. The device reliably scrambles analog signals without compromising radio performance, meeting both tactical flexibility and secure transmission standards. This study contributes a modular analog-based encryption system tailored for the operational environment of the Indonesian Navy, filling a technological void with a user-centered, functional, and scalable solution.